The Political Economy of State Fragility and the Extent to Which It Fuels International Migration Amongst Nigerians. - (:unkn) unknown (My University, 2022)
This thesis examined the political economy of state fragility and the extent to which it fuels international migration amongst Nigerians and adopt a qualitative research method to critically review 15 articles that was identified using the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA). The thesis argues that while migration is not a new phenomenon in Nigeria, there is a renewed fervor amongst Nigerians to migrate and that migration amongst Nigerians is in the context of forced mobility. Employing thematic analysis, the thesis demonstrated how state fragility factors which includes economic factors, sociological factors, geographical factors, and unifying factors (historical, economic, cultural, and political ties) factors fueled international migration amongst Nigerians. This research recommends that a natural progression of this thesis is needed as a cross-national study to compare the political economy of state fragility of Nigeria with another West African country in the state fragile index to examine the extent to which it fuels international migration amongst Nigerians and those in the identified country.
Keywords: International Migration; Migration; Political economy; State fragility